Boosting Sensing Performance of Flexible Piezoelectric Pressure Sensors by Sb Nanosheets and BaTiO3 Nanoparticles Co‐Doping in P(VDF‐TrFE) Nanofibers Mat - Jianqiao Wang; Chaoyu Zhao; Chuan Cao; Miaoxuan Liu; Zhongkang Liu; Peng Zhou; Guocheng Wang; Tianjin Zhang; Lei Zhang; Yajun Qi (Advanced Electronic Materials, 2024)
Abstract Flexible piezoelectric pressure sensors (FPPS) received a lot of attention because of their prominent performance in body motion detection and energy recovery. However, it has faced a huge challenge in manufacturing FPPS with high sensitivity, low cost, and high flexibility. Herein, a ternary flexible nanofiber composite with Sb nanosheets and BaTiO3 nanoparticles as the fillers of P(VDF‐TrFE) is prepared by electrospinning. An impressive open‐circuit voltage of 17.1 V and short‐circuit current of 4.4 µA is obtained based on the composite nanofiber mat at a pressure of 128 kPa with 2 Hz frequency. The FPPS not only exhibit a high sensitivity of 96 mV kPa−1 but also an ultrafast response time of 2 ms. Excellent flexibility and reliability are demonstrated by the unchanged open‐circuit voltage after 2400 cycles. The enhanced FPPS performance is owed to the interfacial polarization effect at the inorganic filler‐organic matrix interface, which also enhances the ferroelectric and dielectric properties. The present FPPS is further confirmed to be a real‐time motion monitor and voice recognizer, which can distinguish various actions and sounds according to distinct output voltage signals and is expected to be used in virtual reality devices, robotic electronic skin, haptic simulation, artificial throat, etc.